Legal Challenges and Policy Solutions in the Development of Village-Owned Enterprises - Taufik, Moh; Rakhmatullah, Bha'iq Roza (Kosmik Hukum, 2025)
Regulation of Tegal Regency No. 2/2018 on Village-Owned Enterprises serves as a regional policy aimed at optimizing village resource potential. This regulation is expected to provide a solution for village development, particularly in Tegal Regency, which possesses significant untapped potential. However, the development of Village-Owned Enterprises often faces challenges due to a lack of stakeholder involvement in policy implementation. Proper execution of this regulation could yield substantial benefits for the community, villages, and the region as a whole. This study employs a normative juridical approach to examine legal issues and policies related to Village-Owned Enterprises. The research aims to analyze the implementation of Tegal Regency Regulation No. 2/2018 and identify solutions to the challenges encountered in its application. Utilizing qualitative data analysis with a descriptive normative juridical method, this study explores the role of various stakeholders in policy implementation. The local government collaborates with the private sector, particularly entrepreneurs, to provide input and motivation for Village-Owned Enterprise development. The findings of this research highlight the importance of evaluating and refining regional policies to enhance their effectiveness. Future studies are encouraged to assess and improve the implementation of Village-Owned Enterprise policies in Tegal Regency, ensuring their optimal contribution to economic development at the community, village, and regional levels.